PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA UMKM ICHA BAKERY TANGERANG SELATAN - Muhammad Al Hazmi; Nani Nani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The purpose of this study is to determine the effect of product quality and price perception on purchasing decisions at Icha Bakery, a small and medium-sized enterprise in South Tangerang. The research method used is quantitative with an associative approach. The population in this study is Icha Bakery consumers, with a sample size of 96 respondents obtained using accidental sampling. Data collection was conducted through questionnaires, while data analysis was performed using simple linear regression and multiple linear regression. The results showed that product quality (X1) and price perception (X2) had a positive and significant effect on purchasing decisions (Y) with the regression equation Y = 13,708 + 0,308 X1 + 0,558 X2. The coefficient of determination had a simultaneous effect of 74,2%. The partial hypothesis test obtained a result for product quality (X1) of t count > t table (7,097 > 1,985), so Ho1 was rejected and Ha1 was accepted. This means that there is a positive and significant effect between the independent variable, namely product quality (X1), and the purchase decision (Y). The partial hypothesis test results for price perception (X2) show that t count > t table (7,589 > 1.985), so Ho2 is rejected and Ha2 is accepted. This means that there is a positive and significant influence between the independent variable, price perception (X2), and the purchase decision (Y). Simultaneous hypothesis testing between product quality (X1) and price perception (X2) variables yielded a result of F count > F table or (113,612 > 3.09). Thus, Ho3 is rejected and Ha3 is accepted, meaning that there is a significant simultaneous effect between product quality (X1) and price perception (X2) on purchasing decisions (Y) at Icha Bakery, a small and medium-sized enterprise in South Tangerang.